Bifurcation of Periodic Solutions of a Delayed SEIR Epidemic Model with Nonlinear Incidence Rate - Bernoussi, Amine (Journal of Applied Nonlinear Dynamics, 2026)
In this paper, we propose the SEIR epidemic model with delay and nonlinear incidence rate. The resulting model has two possible equilibria: if R_0 ≤ 1, then the SEIR epidemic model has a disease-free equilibrium and if R_0 > 1, then the SEIR epidemic model admits a unique endemic equilibrium. By using suitable Lyapunov functionals and LaSalle’s invariance principle, the global stability of a disease-free equilibrium is established. Our main contribution affirms the existence of non constant periodic solutions which bifurcate from the endemic equilibrium when the delay crosses some critical values. Finally, some numerical simulations are presented to illustrate our theoretical results.